Okay, so I expanded the brackets and simplified the equation from (x+4)(x-4)(x-4) to equal(adsbygoogle = window.adsbygoogle || []).push({});

x^{3}-4x^{2}-16x+64 and I needed to sub those values into this equation y=ax^{3}+bx^{2}+cx-d where a=x^{3}b=-4x^{2}c=-16 d=64 which were the values I got from the first equation. I need confirmation If it would be y=x^{6}[/SUP]-4x^{4}-16x^{2}-64

I dunno, it just doesn't seem right.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Linear Equations

**Physics Forums | Science Articles, Homework Help, Discussion**